2022
DOI: 10.1091/mbc.e22-03-0103
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of COPII vesicle formation in yeast characterized by correlative light and electron microscopy

Abstract: Traffic of proteins out of the endoplasmic reticulum (ER) is driven by the COPII coat, a layered protein scaffold that mediates the capture of cargo proteins and the remodelling of the ER membrane into spherical vesicular carriers. Although the components of this machinery have been genetically defined, and the mechanisms of coat assembly extensively explored in vitro, understanding the physical mechanisms of membrane remodelling in cells remains a challenge. Here we use correlative light and electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…The ERES and cis-Golgi are in close proximity in yeast and plants [20,137], though contact sites are only transient in Saccharomyces cerevisiae [138]. COPII-coated vesicles have indeed been clearly visualised in these organisms, providing direct evidence for the mainstream model [139][140][141]. It is instead unclear whether vesicular transport also occurs in metazoa and/or if it is the sole mode of transport.…”
Section: Regulation In Metazoa: the Large Cargo Conundrum And The Rol...mentioning
confidence: 99%
“…The ERES and cis-Golgi are in close proximity in yeast and plants [20,137], though contact sites are only transient in Saccharomyces cerevisiae [138]. COPII-coated vesicles have indeed been clearly visualised in these organisms, providing direct evidence for the mainstream model [139][140][141]. It is instead unclear whether vesicular transport also occurs in metazoa and/or if it is the sole mode of transport.…”
Section: Regulation In Metazoa: the Large Cargo Conundrum And The Rol...mentioning
confidence: 99%
“…For instance, recent research has revealed that high curvature is a prerequisite for retromer to effectively enforce membrane curvature 27 . A pre-requisite for high curvature to facilitate budding is common in other organelles for various coats, including COPI 28 and COPII 29,30 . Our data show that Arp2/3 activity is required for trafficking from endosome to vacuole in fission yeast.…”
Section: Discussionmentioning
confidence: 99%
“…But why would a network of tubules be better than vesicles? Vesicles are seen in yeast 30,31 . However, mammalian cells have a more complex endomembrane organization and different secretory and metabolic needs.…”
Section: Discussionmentioning
confidence: 99%